THE EFFECT OF JOB PROMOTION, WORK DISCIPLINE, ORGANIZATIONAL CULTURE ON WORK PERFORMANCE IN THE REGIONAL REVENUE AGENCY (BAPENDA) IN KEPRI PROVINCE THROUGH JOB SATISFACTION AS INTERVENING VARIABLE - NUSA SETIAWAN PASARIBU, SAPTA (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Promotion of Position, Work Discipline, Organizational Culture, Job Satisfaction, and Work Performance were variables in this study. SEM-PLS is used to analyze data using both parametric and non-parametric statistics (Structural Equation Modeling-Partial Least Square) Research variable data analysis using both parametric and non-parametric statistics, calibration and pilot tests, validity and reliability, analysis of the outer and inner models, and discussion of the findings of hypothesis testing or Path Analysis Path. In this study, route analysis is used to look at the distribution of relationships that show the direct and indirect effects of a variable or collection of variables on other variables. SmartPLS Ver 3.2.9 2022 assists in this study's path coefficient calculation.The findings of this study suggest that Work Performance is positively and negligibly impacted by Job Promotion and Work Discipline. Job Satisfaction Has A Positive And Significant Influence On Work Performance, Job Promotion Has A Positive And Significant Influence On Work Performance, Work Discipline Has A Positive And Significant Influence On Work Performance, Organizational Culture Has A Significant Positive Influence On Employee Work Performance, Job Satisfaction Has A Positive And Significant Influence On Interv Moderating the Impact of Organizational Culture on the Work Performance of the Riau Islands Province's Regional Revenue Agency (Bapenda).